Students’ and Lecturers’ Perceptions in Using Google Translate - Marice Tobo; Sherliane Trisye Poai (Sintuwu Maroso Journal of English Teaching, 2023)
The purpose in this study is to find out the perceptions of students’ and lecturers’ at the English Education Study Program at Sintuwu Maroso University in using Google Translate. The method of the research is quantitative, this research using questionnaire as the instrument in collecting data. The number of respondents is 55 respondents consisting of 42 students and 13 lectures. The questionnaire is adopted from Khusnul Khotimah 2021. The calculation results is obtained that students have dominantly positive perceptions on Google Translate, and lectures dominantly have negative perceptions on Google Translate.